A book found in the trash: the strange case of Roa Bastos’s copy of Julio César Chavez’s El supremo dictador (Anclajes, 2023)
Augusto Roa Bastos conducted considerable research on Doctor Francia, the dictator of Paraguay from 1814 to 1840, during the writing of his great novel Yo el Supremo, published in 1974. Some of the books he consulted ended up in the burn pile of the municipal dump of Chapadmalal, where they were rescued, and eventually brought to Paraguay in July 2022. The most important source for the novel is Julio César Chaves’s El supremo dictador (1942). Starting from some five hundred photographs I took of this book on 28 July 2022, I have been able to reconstruct certain stages of the research and writing of the novel in 1971 and 1972. The Chaves book contained not just underlining and marginalia but also two dozen fragments of typescripts of the novel.
Keywords: Roa Bastos; Doctor Francia; Julio César Chaves; I the Supreme; Genetic Criticism